2016
DOI: 10.2174/0929866523666161130143446
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomics Approach to Discover Drought Tolerance Proteins in Wheat Pollen Grain at Meiosis Stage

Abstract: Plants reproductive phase, when grain yield and consequently farmers' investment is most in jeopardy, is considered as the most sensitive stage to drought stress. In this study, we aimed to explore the proteomic response of wheat anther at meiosis stage in a drought tolerant, Darab, and susceptible, Shiraz, wheat genotypes. Wheat plants were exposed to drought stress at meiosis stage for four days under controlled environmental conditions. Then, anthers from both genotypes were sampled, and their proteomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Previous studies have shown that the overexpression of a 23-kDa ribosomal protein in rice plants was linked to enhanced water use efficiency and increased tolerance to drought stress [ 39 ], while the decreased expression of a 32-kDa ribosomal protein was observed in salt-stressed rice seedlings [ 40 ]. Similar findings have been reported in Arabidopsis , where plastid ribosomal proteins were increased after exposure to short-term salt stress [ 41 ], and also in wheat, where expression levels of ribosomal proteins were found to be different between drought-tolerant and drought-susceptible genotypes [ 42 , 43 ]. The exact nature of the correlation between the abundance of RPs and the drought tolerance of a rice species is still not clear and further investigation is warranted.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that the overexpression of a 23-kDa ribosomal protein in rice plants was linked to enhanced water use efficiency and increased tolerance to drought stress [ 39 ], while the decreased expression of a 32-kDa ribosomal protein was observed in salt-stressed rice seedlings [ 40 ]. Similar findings have been reported in Arabidopsis , where plastid ribosomal proteins were increased after exposure to short-term salt stress [ 41 ], and also in wheat, where expression levels of ribosomal proteins were found to be different between drought-tolerant and drought-susceptible genotypes [ 42 , 43 ]. The exact nature of the correlation between the abundance of RPs and the drought tolerance of a rice species is still not clear and further investigation is warranted.…”
Section: Discussionsupporting
confidence: 84%
“…The 60S and 40S RPs are vital cogs in the stress-defense protein biosynthesis machinery. Previously, RPs were identified to be significantly up-regulated in response to drought stress in wheat [53]. Cysteine synthase is a key enzyme for mediating abiotic stress tolerance through its catalysis in the production of antioxidants and metal chelators, including glutathione and phytochelatin [18].…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics, which is the study of the structural and functional features of all the proteins in an organism, is an important means of understanding complex biological mechanisms, including plant responses to abiotic stress tolerance (Deshmukh et al, 2014). Using transcriptomic or proteomics sequencing, many genes associated with drought response were identified in a number of plants, such as Arabidopsis (Cho et al, 2013; Matsui et al, 2008; Meng et al, 2019), rice (Hamzelou et al, 2020; Li et al, 2019), wheat (Fotovat et al, 2017; Kang et al, 2012; Ma et al, 2017; Michaletti et al, 2018), maize (Zeng et al, 2019; Zheng et al, 2020), soybean (Song, Prince, et al, 2016; Wang & Komatsu, 2018), tobacco (Chen et al, 2019; Khan et al, 2019), and others (An et al, 2020; Ghatak et al, 2017; Jangpromma et al, 2010; Ngara & Ndimba, 2013; Raney et al, 2014; Rodziewicz et al, 2019; Singh et al, 2017; Utsumi et al, 2012; Wisniewski et al, 2009; Yang et al, 2017). In rapeseed, numerous candidate genes associated with drought response have also been identified by transcriptomic and proteomics analyses.…”
Section: Introductionmentioning
confidence: 99%